2010
DOI: 10.1016/j.apsusc.2010.04.109
|View full text |Cite
|
Sign up to set email alerts
|

Ni–P alloy–carbon black composite films fabricated by electrodeposition

Abstract: NiP alloycarbon black (CB) composite films were fabricated by electroplating and their microstructures and properties were examined. The CB and phosphorus contents of the composite films were also investigated. The CB particles were found to be embedded in the NiP alloy matrix. The CB content in the deposits increased, reached a maximum value of 0.77 mass % with increasing CB concentration in the bath up to 10 g dm 3 , and then decreased with a further increase in the CB concentration in the bath.Both befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The reason could be that the TiC nanoparticles are good conductors, and the resulting electric field is stronger around clusters than elsewhere due to increased current density. This observation has been reported by other authors but by using other composites such as Ni-carbon black (CB) and Ni-carbon nanotubes (CNT) [ 24 , 25 ].…”
Section: Resultssupporting
confidence: 81%
“…The reason could be that the TiC nanoparticles are good conductors, and the resulting electric field is stronger around clusters than elsewhere due to increased current density. This observation has been reported by other authors but by using other composites such as Ni-carbon black (CB) and Ni-carbon nanotubes (CNT) [ 24 , 25 ].…”
Section: Resultssupporting
confidence: 81%
“…As it can be clearly seen in Figure 6(a,d,g), the formed intermetallic are dispersed in uniform manner. Incorporation of Sodium dodecyl sulphate surfactant into the plating bath coupled with the application of ultrasonic vibration are responsible for this uniformity [30]. Nevertheless, Chou et al [13] have reported that the application of ultrasonic vibration prior to electrodeposition process is more efficient than introduction of the surfactants.…”
Section: Surface Morphologymentioning
confidence: 99%
“…The particles could be categorized based on their type and properties as metallic particles (such as Ag [164,[166][167][168], Al [169,170], Bi [171], and Ti [172] [123,189], CeO 2 [190], TiN [191,192], Si 3 N 4 [193][194][195], TiCN [196], TiC [163,197], WC [198,199], SiC [200][201][202][203][204][205][206][207][208] [218]). hBN [134,210,211], carbon nano-tubes (CNTs) [180,207,[219][220][221], graphite [222,223], and PTFE [217,[224][225][226][227]).…”
Section: Deposition Of Ni Compositesmentioning
confidence: 99%